2022
DOI: 10.1186/s43045-021-00165-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between perceived social support and body image in women with breast cancer

Abstract: Background Patients with breast cancer have more body image disorders than healthy individuals. The present study aimed to determine the relationship between perceived social support and body image in women with breast cancer. This descriptive-analytical study was performed on 192 women with breast cancer undergoing mastectomy or tumor resection with breast preservation referred to Golestan Hospital in Ahvaz from February 2016 to May 2017. Data collection tools included Demographic Information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Despite undergoing mastectomy and the loss of one or both breasts, the participants did not feel regret or embarrassment about their current appearance because their families consistently offered positive support and accepted their perceived imperfections. This finding corresponds to the research conducted by Doori et al (2022), which highlights the direct relationship between perceived social support and body image in women with breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Despite undergoing mastectomy and the loss of one or both breasts, the participants did not feel regret or embarrassment about their current appearance because their families consistently offered positive support and accepted their perceived imperfections. This finding corresponds to the research conducted by Doori et al (2022), which highlights the direct relationship between perceived social support and body image in women with breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…The mean body image score was higher in women with moderate financial status than in women with low financial status. The study by Doori et al (2022) on women with breast cancer in Iran showed that poor economic status is related to the decrease in body image of these women [ 29 ]. The body image score in women with breast prostheses was significantly higher than in women without breast prostheses.…”
Section: Discussionmentioning
confidence: 99%